Analysis of Tourism Marketing Communication Activities of Srambang Park Ngawi in Increasing Public Awareness - Dianawati, Ervina; Nugrahani, Rah Utami (Prasetiya Mulya Publishing, 2020)
The increasing number of tourist visit is the effect of the increasing ofpublic awareness about the existence of a tourist destination. The increase of awareness is one of the results of marketing communication activities conducted in tourism destination. This study discusses varieties of marketing communication activities conducted in Srambang Park. The aim of this study was to identify tourism marketing communication activities conducted by Srambang Parkof Ngawi City in increasing public awareness. Method used in this research was qualitative descriptive by conducting in-depth interview to five related informants to explain about marketing communication activities, observation and documentation conducted by Srambang Park Ngawi. Marketing communication activities in this study were analyzed using theory of marketing communication by Morissan. According to the results, it can be concluded that Srambang Park Ngawi utilized several marketing communication mix to increase public awareness, among others are advertising in radio, printed media, and social media; marketing promotion through coupons and discounts; public relation and publication through events, and public relations from related agencies; personal sales through presentations from related agencies; direct selling through catalogues from related agencies; and interactive marketing through websites of related agencies.